Overcoming Financing Constraints Through Digital Financial Inclusion: Strengthening Rural Household Entrepreneurship Through E-Commerce: Mengatasi Kendala Pembiayaan Melalui Keuangan Inklusif Digital: Memperkuat Kewirausahaan Rumah Tangga Pedesaan Melalui E-Commerce - Amaliyah, Angguliyah Rizqi; Christianto, Reinardus Dwi Prio; Lestary, Elly; Susilo, Yuvensius Sri; Kusumaningtyas, Metta (Institut Riset dan Publikasi Indonesia, 2026)
Household entrepreneurship plays a strategic role in promoting inclusive rural economic development. However, entrepreneurial activities in rural areas continue to face various constraints, particularly limited access to finance, low levels of financial literacy, and financial exclusion. With the rapid development of digital financial inclusion, these barriers have gradually been reduced through the expansion of technology-based financial services. This community service activity aims to strengthen rural household entrepreneurship through mentoring on the utilization of digital financial inclusion and e-commerce. The implementation method consists of two stages: a pre-activity survey to obtain a descriptive overview of the relationship between trust and digital financial inclusion, followed by entrepreneurial mentoring activities. The survey and mentoring results indicate that the use of digital financial inclusion facilitates entrepreneurial decision-making, alleviates financing constraints, and encourages innovative behavior among household entrepreneurs. Furthermore, the integration of digital financial services with e-commerce serves as a catalyst for expanding market access and enhancing the sustainability of rural household businesses. This community service activity provides practical implications for strengthening community entrepreneurial capacity and supports the formulation of empowerment programs based on digital transformation to foster more inclusive and sustainable rural economic growth.